A composite electrode of 2D‐Ti3C2 (MXene) and polyemeraldine salt of polyaniline for supercapacitor with high areal capacitance. Issue 6 (28th March 2022) - Sarma, Yallapragada Sai Swaroop; Gupta, Nisha; Bhattacharya, Pallab
Abstract: Here, we propose a composite system made of 2D‐Ti3 C2 and two different chemical forms of polyaniline (PANI) like polyemeraldine base (EB) and polyemeraldine salt (ES) to investigate their electrochemical performances as supercapacitor electrode material. Fundamentally, EB and ES are having different functionalities and electrical conductivities to affect their electrochemical performances. Thus, synthesis and electrochemical performances of the composites made of Ti3 C2 and ES or EB with different compositions is discussed where Ti3 C2 /ES form of PANI appears as best performing supercapacitor electrode with the areal capacitance of 1.85 Fcm −2 at 5 mVs −1 . A capacitance enhancement of 5.4 times was observed for Ti3 C2 /PANI‐ES while compared to the same for bare Ti3 C2 with capacity retention of 91.70% after 500 cycles at 1 Ag −1 . This work has also explored the effect of composite compositions by varying the stoichiometric weight ratios of Ti3 C2 and different forms of PANI to achieve high‐performing supercapacitor electrode materials. Abstract : A high‐performing composite supercapacitor electrode of 2D‐Ti3C2 (MXene) and polyemeraldine salt has been prepared with areal capacitance of 1.85 Fcm −2 .